Processo saúde-doença do docente de universidade pública: inquietações sobre o sofrimento psíquico na UFU - Macedo, Abadia de Fátima Rosa (2017)
Having as background the subject of new ways of subjectivity production and its effects on the individual and its social bonds, the overall aim of this research is to examine how Christophe Dejours’ theory could help understanding the health and illness process amongst public university professors. As a result, its specific aims include examining work conditions and working process’ aspects that may cause professors to suffer as well as to systematize characteristics of such suffering at Federal University of Uberlândia so that it may be useful for the planning of actions to promote health among professors. It does so interfaced with the fields of work psychodynamics theory, workers’ health, and sociology of work. The research is supposed to establish a theoretical articulation of occupational health field and the psychodynamics of work theory. Research data were analyzed according to the content analysis approach, in its thematic modality. Five thematic categories were work conditions and work organization, causes of pain and displeasure, detected defenses, symptoms and illnesses; and causes of pleasure and accomplishment. Data were placed within Dejours’ theoretical category of psychic suffering through a comparison of texts this author related to the research’s subject matter and data. This conceptual repertoire was considered in dialogue with occupational health field’s authors and with commentators of university professor suffering and illness as a theme. Results point out new work organization settings whose characteristics and conditions indicate the precariousness of teaching work setting at public universities. This scenario tends to lead professors to withdraw from his/her social function due to sickness. Regarding professors at UFU, results allowed recognizing the existence of psychic illness. Therefore, mental disorders would be indication of pathogen suffering in work settings.